Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1939)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1939)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Annali Lateranensi (Tipografia Poliglotta Vaticana, 1939)
stamp of seminario de s. jose macau

Boletim Official de Macau (1939)
Keywords: 10.Cover Damage; 2.Damage

Boletim Oficial da Colonia de Macau (1939)
Keywords: 1.Conservation 保護; 18.Bookworm

Catalogus Missionis Macaensis (Typographie de la Mission Catholique: Orphelinat de T'ou-sè-wè, 1939)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

COLLECTANEA COMMISSIONIS SYNODALIS (COMMISSION SYNODALIS IN SINIS, 1939)
Keywords: Condition: Fair; Religion

COLLECTANEA COMMISSIONIS SYNODALIS (COMMISSION SYNODALIS IN SINIS, 1939)
Keywords: Condition: Fair; Religion

Decretos, Apendice (Documentos) (Edicao da Uniao Grafica, 1939)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Key to Latin Simplified (Hugo's simplified system, 1939)
Keywords: Latin (Langue) Grammaire Problèmes et exercices; Latin (Langue) Manuels pour anglophones; Latin language; Latin language Grammar; Latin language Grammar Problems, exercises, etc; Latin language Textbooks for foreign speakers English; Latin simplified; Problems and exercises; Textbooks for English speakers

Le Missioni Cattoliche, Bullettino Settimanale Illustrato (1939)
Keywords: 2.Damage

Nouveau dictionnaire Francais-Chinois = 模範法華字典 (The Commercial Press, 1939)
Keywords: French language Chinese Dictionaries

Religiao e Patria (1939)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

The Enthronement of Sacred Heart in the Homes (The Good Pastor Press, 1939)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

十九世紀的偉人 第七冊 安飴的壽終 灰奇保護鮑思高神父 (Herny Valtorta, 1939)

十九世紀的偉人 第五冊 神奇的夢境 (Herny Valtorta, 1939)

十九世紀的偉人 第六冊 異特的靈蹟 (Herny Valtorta, 1939)

十九世紀的偉人 第四冊 陰險的敵謀 (Herny Valtorta, 1939)

Obsequios a Maria para O Mes de Maio - Abranches, J. dos Santos (Libraria Apostolado da Imprensa, 1939)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Dictionnare de Theologie Catholique - Amann, E. (Libraire Letouzey et Ane, 1939)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

我曾经加入过共产党 - B. Liberov, Alexei (紅色小叢書, 1939)

Elementos de gramática ganguela; idioma falado na região do Cubango, Província de Angola, segundo os estudos do Rev[erendo] P[adre] L. Lecomte - Baião, Domingos Vieira; Lecomte, L. (Línguas de Angola, 1939)
Keywords: Ganguela (Langue) Grammaire; Ganguela language Grammar

Archaelogia Biblica - Bea, Augustinus (Pontificium Institutum Biblicum, 1939)
Keywords: 1.Conservation 保護; Fair

最新實用物理學 (上冊) = Black & Davis New Practical Physics - Black, Newton Henry; Davis, Harrey Nathaniel (Commercial Press, 1939)

Portugal em Roma - Casto, Jose de (Uniao Grafica, 1939)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬

Portugal em Roma - Castro, Jose de (Unizo Grafica S. A. R. L., 1939)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Catechism Stories, a Teacher's Aid-Book - Drinkwater, F. H (St. Paul Publications, 1939)
Keywords: 1.Conservation 保護; Fair

Santa Maria e Portugal - Felix, Jose Maria (Unioa Grafica, 1939)
Keywords: 1.Conservation 保護; Good

Pelo Clero de Goa - Figueiredo, Pe. Niceno de (Tipografia Rangel, 1939)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Lições práticas de inglês: novo método de auto-aprendizagem da língua inglesa - Furtado, F. Pinto (L. Bertrand, 1939)

In Dulci Jubilo: Commenti Ceciliani al testo liturgico e al canto gregoriano delle Messe Domenicali e Festive - G. B. Le Guevello (Monfortani, 1939)
Keywords: 14.missing area; Fair

Liturgia: Principios Fundamentais - Gaspar Lefebvre (Livraria Liturgica, 1939)
Stamp of St. Joseph Seminary
Keywords: Good

社會制度的演變 - Godsell, W.; 申生 (社會科學研究社, 1939)
Keywords: Feudalism; Histoire sociale; Social Conditions; Social history; social history

Luz da infância livro de leitura inicial - Herminio, Viriato (D. Barreira, 1939)

Constitution Politique de la République Portugaise - L'Acte Colonial (editions SPN Lisbonne, 1939)
stamp of seminario de s. jose, Macau
Keywords: Good

O Santo Evangelho de Jesus Cristo - Lourenco, P. J (Uniao Grafica, 1939)
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover); 2.Damage

Christ in His Mysteries - Marmion, Columba (Sands and Co., 1939)
Keywords: 1.Conservation 保護; good

A Chave do Ceu - Matos, Jose Lourenco Pereira de (Livraria Figueirinhas, 1939)
Stamp
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

A Minha Viagem para Macau - Monteiro, J. J. (Escola Tipografica Salesiana, 1939)

Lições de Lingua Volume IV: Estudos de Lingua Pátria II - Moreno, Augusto (Estudos de língua pátria, 1939)
Keywords: Examinations; Portugais (Langue) Examens, questions, etc; Portugiesisch; Portuguese language; Portuguese language Examinations, questions, etc

The will of God, by St. Alphonsus Liguori - Murphy, T. A. (Irish Messenger Office, 1939)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Fundamental Sociology - Ross, E. J. (the Bruce Publishing Company, 1939)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover)

Religionsbuchlein, Fur Mutter und Kind - Schlumpf, Marie (Herder &Co. G. m b H. Verlagsbuchhandlung, 1939)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Madre Maria da Paixao - Sousa, P. Luiz de (Tipografia das Missoes Franciscanas, 1939)
Keywords: 1.Conservation 保護; Good

給兒童們 - Stanilaus, S. J. (Catholic Truth Society (真理學會), 1939)

Dicionário português latino - Torrinha, Francisco (D. Barreira, 1939)
Keywords: Dicionario; Latim; Língua latina dicionário; Língua portuguesa dicionário; Portugues

新中国教科書高級中学平面解析几何學 - 余介石; 何魯 (正中書局, 1939)
Keywords: 平面几何:解析几何 高中; 解析几何:平面几何 高中

復興初級中學教科書 國文 (第一冊) - 傅, 東華 (國民政府教育部審定, 1939)

復興初級中學教科書 國文 (第三冊) - 傅, 東華 (國民政府教育部審定, 1939)

復興初級中學教科書 國文 (第二冊) - 傅, 東華 (國民政府教育部審定, 1939)

復興初級中學教科書 國文 (第五冊) - 傅, 東華 (國民政府教育部審定, 1939)

復興初級中學教科書 國文 (第四冊) - 傅, 東華 (國民政府教育部審定, 1939)

復興初級中學教科書 物理學 (下冊) - 周, 頌久 (國民政府教育部審定, 1939)

動物学 上册 - 周建人 (復興初級中學教科書, 1939)
Keywords: 动物学 初中 教材

英漢模範字典: 求解作文兩用 - 張, 世鎏; 平, 海瀾; 厲, 志雲; 陸, 學煥 (Commercial Press, 1939)

田間詩選 - 張援 (商務印書館, 1939)
Keywords: Agriculture; Agriculture Poetry; Agriculture Poésie; Chinese poetry (Selections: Extracts, etc.); Poetry

兒童世界 第四十四卷 第六期 新一八〇號 - 徐, 應昶 (小學生戰時常識書叢, 1939)

common errors in english composition with corrections=英文作文通常錯誤指正 - 慎, 微之 (chiu yih, 1939)

辭源: 正續編合訂本 - 方毅 (商務印書館, 1939)
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries; Dictionary; Dictionnaires; dictionaries

文英中譯法 - 曹, 漣君 (啟明書局, 1939)

音樂的基礎知識 - 朱, 穌典 (中華書局, 1939)
Keywords: Music Instruction and study; Musique Étude et enseignement

高中英語讀本第三冊=New Standard English Readers for Senior Middle Schools - 李, 儒勉 (中華書局, 1939)

蜜蜂瑪雅的冒險 - 波守斯著 ; 段可情譯.; Bonsels, Waldemar (少年知識叢書, 1939)
Keywords: Tong hua de guo; Wen xue jin dai shi jie zuo pin zong he ji

實驗初中國文 第五冊 - 王, 頌三 (修正課程標準適用 初級中學學生用, 1939)

俄語一月通 - 舒, 重野 (世界語言學社, 1939)
Keywords: Russian language Study and teaching Chinese speakers; 俄語 學習及教學 漢語人士

全國現代高中作文精華 (第四冊) - 馬, 祟淦; 吳, 實經 (勤奮書局, 1939)

A L'ecole de Mere Marie de la Passion, Les Franciscaines Missionnaires de Marie (Imp. Francisc Miss, 1938)
Keywords: 1.Conservation 保護; Good

Boletim Offical da Colonia De Macau (1, 1938)
Keywords: 18.Bookworm; 2.Damage

Boletim Oficial da Colonia de Macau (1938)
Keywords: 1.Conservation 保護; 18.Bookworm

Documenta Sanctae Sedis, recentiora-selecta de re missionaria (E secretaria Generali in Aedibus S. C. de Propaganda Fide, 1938)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Ecos de Shiuhing (1938)
Keywords: 1.Conservation 保護; Good

Enchiridion Clericorum (Typis Polyglottis Vaticanis, 1938)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm (Only Cover)

Manuel D'etudes Bibliques (Pierre Tequi, Libraire-editeur, 1938)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Manuel D'etudes Bibliques (Pierre Tequi, Libraire-editeur, 1938)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

O Catechista Pratico (Petropolis, Estado do Rio, 1938)
Keywords: 1.Conservation 保護; Fair

Religiao e Patria (1938)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

The small missal (Burns Oates and Washbourne, 1938)
hand-writting
Keywords: 10.Cover Damage; Good

華僑戰線 第一卷第五六期合刊 (華僑抗敵動員總會宣傳委員會出版組, 1938)
华侨宣传抗日刊物。本刊主要报道各地华侨救亡动态，动员华侨发扬爱国传统，投身抗战救国斗争，捐资出力，争取抗日战争的最后胜利。其中第1卷第2期载有宋庆龄、何香凝联名发起的"致海外侨胞书"。

Synopsis Theologiae Dogmaticae - AD. Tanquerey (Typis Societatis sancti Joannis Evangelistae, Desclée et socii, 1938)
Stamp of unknown
Keywords: Fair

Mon Catechime Vecu - Bayonne, Houbaut Eveque de (P. Lethielleux, Editeur, 1938)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Mon Catechime Vecu - Bayonne, Houbaut Eveque de (P. Lethielleux, Editeur, 1938)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Mon Catechime Vecu - Bayonne, Houbaut Eveque de (P. Lethielleux, Editeur, 1938)
Keywords: 1.Conservation 保護; 15.Stain 污漬

A Devocao ao Coracao Apostolico de Jesus Alma da Acao Catolica - Bosch, Victor van Den (Pia Sociedade de Sao Paulo, 1938)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

Sainte Bible - Crampon, Chanoine A. (Societe de Saint Jean l'Evangeliste, 1938)
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Participacao Ativa Na Missa - Francois, Dom Augustin (Edicoes Lumen Christi, 1938)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃.

A New English Letter-Writer=新撰英文尺牘 - G. K. KE, Hertz (The Kaiming Book Company, Ltd., 1938)

Casus Conscientiae Propositi ac Soluti - Genicot, Eduardo (L'edition Universelle, S. A., 1938)
Signature
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Les Latins Pages Principales des Auteurs du Programme - Georgin, Ch. (Librairie Hatier, 1938)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Les Latins: pages principales des auteurs du programme - Georgin, Charles (Hatier, 1938)
Keywords: Latin (Langue) Lectures et morceaux choisis

Je parle français! (Cours élémentaire). Dessins de Myrac - Guyot, Marcel; Deydier, J.; Jolivet, B. (Impr. et libr. Emmanuel Vitte, 3, place Bellecour, 1938)

Acto Heroico a Favor das Almas do Purgatorio - J. M. B. L. (Composto e Impresso, 1938)
Signature
Keywords: 1.Conservation 保護; Good

Supplement au Dictionnaire de La Bible - Louis Pirot (Librairie Letouzey et Ane, 1938)
Stamp of St. Joseph Seminary
Keywords: Good

Lições de Lingua Volume III: Estudos de Lingua Pátria II - Moreno, Augusto (Estudos de língua pátria, 1938)
Keywords: Examinations; Portugais (Langue) Examens, questions, etc; Portugiesisch; Portuguese language; Portuguese language Examinations, questions, etc

Praelectiones Biblicae ad Usum Scholarum - Simon, Hadridano (Ex Off. Libraria Marietti, 1938)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Meditacoes praticas - Vercruysse, P. Bruno (Edicoes do Apostolado da Imprensa, 1938)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Meditacoes Praticas, Para todos os dias do ano - Vercruysse, P. Bruno (Eidcoes do Apostolado da Imprensa, 1938)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

復興初級中學教科書 幾何 (上冊) - 余, 介石; 徐, 子豪 (國民政府教育部審定, 1938)

復興初級中學教科書 幾何 (下冊) - 余, 介石; 徐, 子豪 (國民政府教育部審定, 1938)

復興高級中學教科書 物理學 (下冊) - 周, 壽昌 (國民政府教育部審定, 1938)

修正課程標準適用 開明算術教本 (下冊) - 周, 為羣 (初級中學學生用, 1938)

英漢模範字典: 求解作文兩用 = Model English-Chinese dictionary with illustrative examples - 張世鎏 (Commercial Press, 1938)
Keywords: Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language--Dictionaries--Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English, English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language--Dictionaries--English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; Dictionnaires multilingues; English language

開明物理學敎本 上冊 - 戴運軌 (開明書店, 1938)
Keywords: Physics; Physique; physics

開明物理學敎本 下冊 - 戴運軌 (開明書店, 1938)
Keywords: Physics; Physique; physics

文件 - 班台萊耶夫著 ; 夏懿譯.; Panteleev, L. (生活書店, 1938)

英文最常用成語650 - 謝, 克任 (啟明書局, 1938)

國學概論 (上) - 錢, 穆 (商務印書館, 1938)
Keywords: China; Learning and scholarship; Learning and scholarship China; Savoir et érudition Chine

國學概論 (下) - 錢, 穆 (商務印書館, 1938)
Keywords: China; Learning and scholarship; Learning and scholarship China; Savoir et érudition Chine

英文最常用成語650 - 陳, 徐堃 (啟明書局, 1938)

復興初級中学教科書算術 (上册) - 駱, 師曾 (Commercial Press (商務印書館), 1938)
Keywords: 算术 初中

Boletim Official de Macau (1937)
Keywords: 18.Bookworm; 2.Damage

Caeremoniale Iuxta Ritum Romanum seu De Sacris Functionibus (Officina Libraria Marietti, 1937)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Collectanea Commissionis Synodalis (Kwantungtien Hutung, 1937)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

De Imitatione Christi Libri Quatuor (Typis Societatis Missionum Ad Exteros, 1937)
Keywords: 1.Conservation 保護; Good

Mission Manual of the Vicariate of Kongmoon ( South China) (Nazareth Press, 1937)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Pastoral Festas (largo de camoes, 1937)
hand writting, sign

Religiao e Patria (1937)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Casus Conscientiae Decreta et Monita - Anno (St. Louis Industrial School, 1937)
Keywords: Fair

Santo Antonio de Lisboa na Tradicao Popular - Armando de Mattos (Livraria Civilizacao, 1937)
Stamp of St. Joseph Seminary
Keywords: Fair

Imitacao do Sagrado Coracao de Jesus - Arnold, P. J. (Edicoes do Apostolado da Imprensa, 1937)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Manual de Harmonia - Borba, Tomaz (Valentim de Carvalho, 1937)

Synopsis Theologiae Dogmaticae Fundamentalis - Bord, J. B. (Typis Societatis S. Joannis Evang., 1937)
Signature
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

D. Joao V ea Santa Se - Brazao, Eduardo (Coimbra Editora, L. Da, 1937)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

De bello gallico de César - Caesar, Julius (Livraria sà da Costa, 1937)
Keywords: 58-51 B.C; Europe Gaul; Gaul History Gallic Wars, 58-51 B.C; Gaule Histoire 58-51 av. J.-C. (Guerre des Gaules); History

Hei de Ser Sacerdote? - Casimiro, Acacio (Editor- Apostolado da Imprensa, 1937)
Keywords: 1.Conservation 保護; Good

Santo Incio de Loiola, Fundador da Companhia de Jesus - Daurignac, J. M. S. (Apostolando da Imprensa, 1937)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 6.Yellowing 變黃

A Accao Catolica Portuguesa - Felix, Jose Maria (1937)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Gramática Latina de Dr. Iohan Nicolai Madvig - Firmino, Nicolau (Livraria Avelar Machado, 1937)

Storia Della Teologia Cattolica - Grabmann, Martino (Societa Editrice Vita e Pensiero, 1937)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

A dictionary of English idioms. Part 1: Verbal idioms - Henderson, B. L. K. (James Blackwood, 1937)
Keywords: Anglais (Langue) Mots et locutions; Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language--Dictionaries--Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English, English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language--Dictionaries--English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; English language; English language Idioms; English language Terms and phrases; English language Verb

航空常識問答 - Henshaw, P. M. (商務印書館, 1937)
Keywords: 航空 基本知识

Quaestiones Seleciae Ex Historia Ecclesiastica, 1200-1640 - Leiber, P. R. (Copisteria, Velox Via Pie di Marmo, 1937)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; fair

將来的世界 - Low, A. M. (Commercial Press (商務印書館), 1937)
分24章, 論述未來的空中旅行, 電動馬達與自動車, 無線電與電視, 以及未來的法律, 宗教, 教育, 家庭, 天氣, 城市等
Keywords: 未来学

I Promessi Sposi - Manzoni, Alessandro (Edizioni Aurora, 1937)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Jesus Christo nos seus Misterios - Marmion, D. Columba (Oficnas Graficas da Pax, 1937)
Signature
Keywords: 1.Conservation 保護; 18.Bookworm

Ciências, Geográfico-Naturais: 1.⁰, 2.⁰, e 3.⁰ anos dos liceus - Mattoso, Antonio G.; D' Athayde, A;varo (Livraria Sá da Costa, 1937)

Gramática latina: acomodada aos programas oficiais - Miranda, Manuel Francisco de; Cunha, Arlindo Ribeiro da (Seminário de Braga, 1937)
Keywords: Latín (Lengua) Gramática

Lições de Lingua Volume I: Estudos de Lingua Pátria II - Moreno, Augusto (Estudos de língua pátria, 1937)
Keywords: Examinations; Portugais (Langue) Examens, questions, etc; Portugiesisch; Portuguese language; Portuguese language Examinations, questions, etc

Lições de Lingua Volume II: Estudos de Lingua Pátria II - Moreno, Augusto (Estudos de língua pátria, 1937)
Keywords: Examinations; Portugais (Langue) Examens, questions, etc; Portugiesisch; Portuguese language; Portuguese language Examinations, questions, etc

Patrologia seu Historia Antiquae Litteraturae Ecclesiasticae - Steidle, Basilio (Typis Herderianis Frigurgi Brisgoviae, 1937)
Keywords: 1.Conservation 保護; Good

Historia Dos Congressos Eucaristicos - Teixeira, Pe. Manuel (und, 1937)

Dicionário Latino-Português (Marânus, 1937)
Keywords: Dictionaries; Latin dictionaries Dictionaries Portuguese; Portuguese language; Portuguese language Dictionaries Latin

漢英大辭典 = A complete Chinese-English dictionary - Tsang, O. Z. (Republican Press, 1937)
Keywords: Chinese language; Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language--Dictionaries--Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English, English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language--Dictionaries--English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries

Beato Joao de Brito, da Companhia de Jesus - Vasconelos, Evaristo de (Editor- Apostolado da Imprensa, 1937)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

拉丁文初學: 課本 = Rudimenta Linguæ Latinæ Exercitia - Weig, D. G.; De Tsingtao, Apost.; Mittler, R. P. Th. (Typis Miss. cathol., 1937)
Keywords: 拉丁字母

高中物理學 上册 - 仲光然 (中華書局, 1937)
Keywords: 物理 高中 教材

修正課程標準適用 新編高中平面幾何學 (上冊) - 余, 介石 (教育部審定, 1937)

建國教科書 高級中學 平面解析幾何學 - 余, 介石 (教育部核定, 1937)

新編高中平面幾何學 (上册) - 余, 介石 (中華書局, 1937)
Keywords: 平面几何 高中

向耶穌聖靈誦 - 吳, 應楓 (聖時默想, 1937)

動物学 下册 - 周建人 (復興初級中學教科書, 1937)
Keywords: 动物学 初中 教材

初中物理 上冊 - 張開圻; 包墨靑.; 陶鴻翔. (修正課程標準適用, 1937)

初中物理 下冊 - 張開圻; 包墨靑.; 陶鴻翔. (修正課程標準適用, 1937)

非常時期之模范人物 - 徐楚樵. (Zhong guo xin lun she fei chang shi qi cong shu, 1937)

小学音樂教材初集. 低年級之部 - 教育部 (中華書局, 1937)
Keywords: 音乐 小学 教材

京注音複式詳解中華新字典 - 王, 頌棠 (環球書局, 1937)
Keywords: Chinese language; Chinese language Dialects; Chinese language Dialects China Canton (Kuang Tung Province); Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries; 漢語 字典; 漢語 方言 中國 廣州 (廣東省)

中華新字典: 京粤注音複式詳解 - 王頌棠 (環球書局, 1937)
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries

京注音複式詳解中華新字典 - 王頌棠 (環球書局, 1937)
Keywords: Chinese language; Chinese language Dialects; Chinese language Dialects China Canton (Kuang Tung Province); Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries; 漢語 字典; 漢語 方言 中國 廣州 (廣東省)

清代七百名人傳 上冊 - 蔡, 丐因 (世界書局, 1937)
Keywords: 1644-1912; Biographies; China; China Biography; China History Qing dynasty, 1644-1912 Biography; Chine Histoire 1644-1912 (Dynastie des Qing) Biographies; History; Qing Dynasty (China); collective biographies

清代七百名人傳 下冊 - 蔡, 丐因 (世界書局, 1937)
Keywords: 1644-1912; Biographies; China; China Biography; China History Qing dynasty, 1644-1912 Biography; Chine Histoire 1644-1912 (Dynastie des Qing) Biographies; History; Qing Dynasty (China); collective biographies

清代七百名人傳 中冊 - 蔡, 丐因 (世界書局, 1937)
Keywords: 1644-1912; Biographies; China; China Biography; China History Qing dynasty, 1644-1912 Biography; Chine Histoire 1644-1912 (Dynastie des Qing) Biographies; History; Qing Dynasty (China); collective biographies

新字典 - 許伏民 ((民光)群學書社, 1937)
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries

新編高中本國史 (上冊) - 金, 兆梓 (中華書局, 1937)
Keywords: China; China History; Chine Histoire; History

初中動物 上冊 - 陳, 綸; 華, 汝成 (修正課程標準適用, 1937)

初中動物 下冊 - 陳, 綸; 華, 汝成 (修正課程標準適用, 1937)

標準國音學生新字典 - 顧佛影; 黎錦暉 (中央書店, 1937)
收九千餘字. 按部首編排. 書前編者自序寫于1935年3月
Keywords: Chinese language; Chinese language Dictionaries, Juvenile; Chinois (Langue) Dictionnaires pour la jeunesse; Dictionaries; Juvenile works

A Missa e a Vida Interior (Edicao da Opus Dei, 1936)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Boletim Official de Macau (1936)
Keywords: 18.Bookworm; 2.Damage

Collectanea Commissionis Synodalis (Kwantungtien Hutung, 1936)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

Collectanea Commissionis Synodalis (Kwantungtien Hutung, 1936)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

Enciclica de S. S. Pio Pio XI, Ad Catholici Sacerdotii (Mensageiro do Coracao De Jesus, 1936)
Keywords: 1.Conservation 保護; 10.Cover Damage

Expositiones In Sancta Evangelia (Typis Nazareth, 1936)
Keywords: 1.Conservation 保護; 2.Damage

Expositiones in Sancta Evangelia (Ex Typis Nazarethanis Societatis Missionum ad Exteros, 1936)
Keywords: 1.Conservation 保護; Good

Expositiones in Sancta Evangelia (Ex Pis Nazarethanis Societatis Missionum ad Exteros, 1936)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Expositiones in Sancta Evangelia (Ex Typis Nazarethanis Societatis Missionum ad Exteros, 1936)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Expositiones in Sancta Evangelia, Ouae Leguntur intra Missam, Diebus Dominicis (Ex Typis Nazarethanis Societatis Missionum ad Exteros, 1936)
Keywords: 1.Conservation 保護; Good

Expositiones in Sancta Evangelia, Quae Leguntur intra Missam (Ex Typis Nazarethanis Societatis Missionum ad Exteros, 1936)
Keywords: 1.Conservation 保護; 2.Damage

Fatima, em 65 Vitas (Album do Santuario, 1936)
Keywords: 1.Conservation 保護; Good

Licoes de Teologia Pastoral (Tipografia Andrade, 1936)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Manuel D'etudes Bibliques (Piere Tequi, Libraire- Editeur, 1936)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Manuel D'etudes Bibliques (Pierre Tequi, Libraire-editeur, 1936)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Meditacoes, Afectivas e Praticas, Sobre of Evangelho (Livraria Editora Educacao nacional, 1936)
Keywords: 1.Conservation 保護; Good

Meditacoes, Afectivas e Praticas, Sobre of Evangelho (Livraria Editora Educacao nacional, 1936)
Keywords: 1.Conservation 保護; Good

Religiao e Patria (1936)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Sacerdotalia (Printed at the Codialbail Press, 1936)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

The Devotion of The Nine Tuesdays of St. Anthony of Padua (The Anthonian Press Temple Street, 1936)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

防毒講話 (軍政部學兵隊, 1936)
Keywords: 中毒-化学武器 预防; 化学武器-中毒 预防

Dictionnare de Theologie Catholique - Amann, E. (Libraire Letouzey et Ane, 1936)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Praelectiones Elementariae Litugiae Sacrae - Bousquet, P. (St. Louis Industrial School Printing Press, 1936)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Sao Paulo - Camargo, Paulo Florencio da Silveira (1936)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Vida de Santa Luiza de Marillac - Castro, Jeronimo de (Editora Vozes, 1936)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

Manual de Accao Catolica - Civardi, Luis (Tipografia Porto Medico, 1936)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Summa Iuris Canonici - Felice M. Cappello S. J. (Universitatis Gregorianae, 1936)
Stamp of unknown

A Vitima do Calvario - Felix, Jose Maria (Tipografia das Oficinas de S. Jose, 1936)
Signature
Keywords: 1.Conservation 保護; 10.Cover Damage

O Culto d Nossa Senhora da Paz na Ilha de Sam Miguel - Ferreira, P. Ernesto (Empresa Tipografica Limitada, 1936)
Signature
Keywords: 1.Conservation 保護; Good

Everybody's favorite easy pieces for the violin, with piano accompaniment - Fischel, Max (Everbody's favorite series, 1936)
Keywords: Violin music; Violon, Musique de

Ad Catholici Sacerdotii - Fontes, J. Ferreira (Mensageiro do Coracao De Jesus, 1936)
Keywords: 1.Conservation 保護; good

Bible History containing the Most Remarkable Events of the Old and New Testaments - Gilmour, Richard (Benziger Brothers, Inc, 1936)
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Vallant Women, Mother Mary ofthe Passion and the Franciscan Missionaries of Mary - Goyau, Georges (Sheed & Ward, 1936)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

L'heure du Matin ou Meditations Sacerdotales - Gros, I'Abbe J. B (Pierre Tequi, Libraire-editeur, 1936)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Enchiridion Asceticum - Journel, M. J. Rouetde; Dutilleul, J. (Typis officinae Grafos, 1936)
Keywords: 1.Conservation 保護; Good

Missionariois! - Manna, Paulo (Escola Tipografica das Missioes, 1936)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Vieira-Prègador : Estudo Filosófico da Eloqüência Sagrada segundo a vida e as Obras do Grande Orador Português - P. Luís Gonzaga Cabral (Livraria Cruz, 1936)
hand-writting
Keywords: Good

De Matrimonio in Missionibus ac Potissimum in Sinis, Tractatus Practicus et Casus - Payen, G. (In Typographia T'Ou- Se- We, 1936)
Signature
Keywords: 1.Conservation 保護; Good

De Matrimonio in Missionibus ac Potissimum in Sinis, Tractatus Practicus et Casus - Payen, G. (In Typographia T'Ou- Se- We, 1936)
Signature
Keywords: 1.Conservation 保護; Good

Pitman's book of synonyms and antonyms - Pitman (Pitman, 1936)
Keywords: English language Synonyms; English language Synonyms and antonyms

論聖教會的教育 - Pope Pius XI (教宗通牒, 1936)
Keywords: Catholic Church; Catholic Church Education; Education; Église catholique Éducation

Enchiridion Iuris Canonici - Sipos, Stephanus (Ex Typographia, Haldas R. T., 1936)
Signature
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Expositiones in Sancta Evangelia - Thiriet, Juliano M. Ap. (Ex Typis Nazarethanis Societatis Missionum ad Exteros, 1936)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

De Sacrae Scripturae Inspiratione - Tromp, Sebastianus (1936)
Keywords: 1.Conservation 保護; 2.Damage

Bilingual Model Letter Writing=學生課外讀物 英漢對照 模範書信 - Tung, Chien Chih (The Chun Ming Book Co. (春明書店), 1936)

孟子集註 (新文化書社, 1936)

高级中学几何教科书. 下册 - 吴在渊; 胡敦复 (中華書局, 1936)
Keywords: 几何 高中

周作人文選 - 周, 作人 (仿古書店, 1936)

生活的科學 - 安, 德婁 (漢譯世界名著, 1936)

言文對照 中庸 - 廣智書局編輯部 (言文對照四書 = 大學.中庸.論語.孟子, 1936)

言文對照 大學 - 廣智書局編輯部 (言文對照四書 = 大學.中庸.論語.孟子, 1936)

中等數學選編 四版增訂本 - 徐, 甘棠; 張, 兆駟 (知用中學出版社, 1936)

世界語初級講義 - 樂, 嘉煊 (中國世界語函授學社, 1936)
Keywords: Esperanto; Esperanto Textbooks for Chinese speakers; Textbooks for Chinese speakers

英漢求解作文文法辨義四用辭典 = A daily use English-Chinese dictionary - 詹文滸 (世界書局, 1936)
Keywords: Ying yu han yu ci dian

藝術漫談 - 豐子愷 (人間書屋, 1936)
Keywords: Art

聖歎批選古文必讀 - 金, 聖嘆 (天下才子必讀, 1936)
Keywords: 古典散文 选集 中国

聖歎批選唐詩 - 金聖嘆 (天下才子必讀, 1936)
分16类, 所选自《左传》起至宋止, 每篇前有批语, 文中还有夹批. 收末附《圣叹尺牍》
Keywords: 古典散文 选集 中国

晚宋民族詩硏究 - 陳灼如 (Guo xue cong kan, 1936)
Keywords: 960-1279; Chinese poetry; Chinese poetry Song dynasty, 960-1279 History and criticism; Cong shu min guo zhong guo; Criticism, interpretation, etc; Gu dian shi ge yan jiu song dai zhong guo; Poets, Chinese; Poètes chinois; Poésie chinoise 960-1279 (Dynastie des Song) Histoire et critique; Song Dynasty (China)

祟修引撮要 - 黃臬, 波莫 (Summarium de Perpectione Christiana, 1936)

Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1935)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Atti de Pellegrinaggio-Congresso delle Infermiere Cattoliche (Citta del Vaticano, 1935)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Boletim Official de Macau (1935)
Keywords: 18.Bookworm

Brevissimo Catecismo para a Comunhao Particular (Tipografia da Missao do Padroado, 1935)
Keywords: 1.Conservation 保護; Fair

Expositiones in Sancta Evangelia, Ouae Leguntur intra Missam, Diebus Dominicis (Ex Typis Nazarethanis Societatis Missionum ad Exteros, 1935)
Keywords: 1.Conservation 保護; Good

Expositiones in Sancta Evangelia, Ouae Leguntur intra Missam, Diebus Dominicis (Ex Typis Nazarethanis Societatis Missionum ad Exteros, 1935)
Keywords: 1.Conservation 保護; Good

Litterae Encyclicae, Aeterni Patris, Leonis Papae XIII, De Philosophia Scholastica (Commission Synodalis in Sinis, 1935)
Stamp
Keywords: 1.Conservation 保護; Fair

O Lirio de Canossa (Escola Tipgrafica do Orfanato da Imaculada, 1935)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Religiao e Patria (1935)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

The ideal pocket Webster dictionary: self-pronouncing (World Syndicate Pub. Co., 1935)
an authoratative dictionary ..
Keywords: Anglais (Langue) Dictionnaires; Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language--Dictionaries--Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English, English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language--Dictionaries--English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; English language

厄斯德爾: 劇本 (德育小說, 1935)

民教半月刊 第七期 (廣東省立民眾教育館, 1935)

De Deo Uno et Trino, commentarius in Primam Partem - Billot, Ludovico (Apud Aedes Universitatis Gregorianae, 1935)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Pontos de Exame de Latim 7ª Classe Precedidos dum Resumo Gramatical - E Sousa, Campos (Livraria Pacheco, 1935)

Latinae grammaticae medulla - Echániz, Joseph (Seminarium Minus Sacratissimi Cordis Iesu, 1935)
Keywords: Lingua e letteratura latina Linguistica - Grammatiche - Metodi

Dicionário Inglês-Português - Ferreira, Júlio Albino (The Teacher at home, 1935)
Keywords: Dicionarios Bilingues Ingles/Portugues; Dictionaries; Dictionnaires multilingues; English language; English language Dictionaries Portuguese; Multilingual dictionaries; polyglot dictionaries

Praeelectiones Theologieae Asceticae - Fiocchi, Ambrosius M. (Typis Pont. Universitatis Gregorianae, 1935)
Signature
Keywords: 1.Conservation 保護; Good

Dictionnaire latin-français - Gariel, A. (A. Hatier, 1935)
Keywords: Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language--Dictionaries--Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English, English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language--Dictionaries--English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries

Música - Gonzaga Aires Mariz, P. Liiz (Escola Tipografica Salesiana, 1935)

文學概論 - Hunt, Theodore Whitefield (漢譯世界名著, 1935)
Keywords: 文學理論

Cliches usuels de la langue Mandarine .. - Kervyn, Louis M. (Scheut mission, 1935)
Keywords: Chinese language; Chinese language Conversation and phrase books; Chinese language Dialects Mandarin; Conversation and phrase books

Seminario Patriarcal de Rachol - Liciano , C. Joao Sousa (1935)
Keywords: 1.Conservation 保護; 2.Damage

Bibliotieca Lusitana - Machado, Diogo Barbosa (Na Officina Patriarcal de Francisco Luiz Ameno, 1935)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Bibliotieca Lusitana - Machado, Diogo Barbosa (Na Officina Patriarcal de Francisco Luiz Ameno, 1935)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Novum Testamentum, Graece et Latine - Merk, Augustinus (Sumptibus Pontiecii Instituti Biblici, 1935)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Summa Theologiae Moralis - Noldin, H. (Eidtorial Herder, 1935)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Summa Theologiae Moralis, de Sexto Praecepto et de Usu Matrimonii - Noldin, H. (Typis et Sumptibus Feliciani Rauch, 1935)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

A Hollanda - Ortigão, Ramalho (A.M. Pereira, 1935)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair

Illustrated Bible History of the Old and New Testaments, for the use of Chatholic Schools - Schurster, Ignatius. (Herder Publications, 1935)
Stamp
Keywords: 18.Bookworm

Moderno Dicionario da Lingua Portuguesa - Torrinha, Francisco (Libraria Simoes Lopes, 1935)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm

Moderno Dicionario da Lingua Portuguesa - Torrinha, Francisco (Libraria Simoes Lopes, 1935)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm

O Liceu em Casa Publicação Dirigida: Pontos de Exame Resolvidos e por Resolver: Latim - V., P. (Livraria Simões Lopes, 1935)

II Pars. Epistulae S. Pauli, - Vitti. A (1935)
Stamp of the St. Joseph Seminiary
Keywords: 10.Cover Damage; 2.Damage

漢譯溫氏高中代數學 - Wentworth, G. A. (商務印書館, 1935)

天主教 - 劉, 韻軒 (中華公教進行會總監督處, 1935)
Keywords: Tian zhu jiao

復興初級中學教科書 三角 - 周, 元瑞; 周, 元谷 (國民政府教育部審定, 1935)

現代初中教科書 幾何 (上冊) - 周, 宜德 (商務印書館, 1935)

現代初中教科書 幾何 (下冊) - 周, 宜德 (商務印書館, 1935)

現代初中教科書 幾何 (上册) - 周, 宣德; 段, 育華 (商務印書館, 1935)
Keywords: 平面几何 初中

書目答問 - 張, 之洞 (國學基本叢書, 1935)
Keywords: Bibliographies; Chinese literature; Chinese literature Bibliography; Littérature chinoise Bibliographie

國學常識答問 - 張振鏞. (商務印書館, 1935)
Keywords: China; China Study and teaching; Chine Étude et enseignement; Education

標準國音學生字典 - 張文治 (中華書局, 1935)
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries

康熙字典: 附康熙字典備考及補遺 - 張玉書 (商務印書館, 1935)
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries; Dictionnaires; dictionaries

徐文長全集 (大道書局, 1935)

湯若士全集 三 - (明) 湯顯祖著. (大道書局, 1935)

湯若士全集 二 - (明) 湯顯祖著. (大道書局, 1935)

湯若士全集 四 - (明) 湯顯祖著. (大道書局, 1935)

湯若士全集 一 - 湯, 顯祖 (大道書局, 1935)

詳註孝經 - 王, 文英 (大逹圖書供應社 : 託售所廣益書局, 1935)

註解孝經 - 王, 英文 (大連圖書供應社, 1935)

地球之滅亡 - 石井, 重美 (自然科學小叢書, 1935)
Keywords: Earth (Planet); Terre

中學國文課本菁華 (第一冊) - 翰飛, 鄒弢 (土山灣印書館, 1935)

彌撒舊聞 - 茅, 本荃 (土山灣印書館, 1935)
Keywords: Mass; Messe; eucharists

代數學 上册 - 虞, 明禮 (商務印書館, 1935)
Keywords: 代数 高中 教材

代數學 下册 - 虞, 明禮 (商務印書館, 1935)
Keywords: 代数 高中 教材

魔鬼的鎖鏈 - [西]加尔德荣(P. Calderon de la Barca)著.; 加尔德荣.; Calderon de la Barca, P. (西什庫遣使会印書館, 1935)
Keywords: USJ SEMINARY LIBRARY PROJECT; 戏剧 剧本 近代

詩經讀本 - 鍾際華 (大文書局, 1935)
Keywords: Shi jing

疇人傳(下) - 阮, 元 (國學基本叢書, 1935)

耶穌的小朋友 - 陳, 田 (聖体軍小叢書, 1935)
Keywords: 儿童文学 长篇小说 中国 现代

Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1934)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Boletim Official de Macau (1934)
Keywords: 18.Bookworm

Boletim Official de Macau (1934)
Keywords: 18.Bookworm

Le Sacre Ceremonie secondo il Rito Romano per tutti i tempi dell'anno (Libreria Francesco Ferrari, 1934)
sign
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; poor

Maddalena di Canossa, Fondatrice Delle Figlie e Dei Figli Della Carita (Soc. Tip. A. Macioce & Pisani, 1934)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 6.Yellowing 變黃

Manuel D'etudes Bibliques (Piere Tequi, Libraire- Editeur, 1934)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Religiao e Patria (1934)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Syntaxis Linguae Latinae Exercitia (Typis Miss. Cathol., 1934)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Execicios de Sto Incio e Leituras Espirituais - Amaral, Miguel de (Edicoes A. J. Trav. da Carvalhosa, 1934)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Exercicios de Sto Incio Leituras Espirituais - Amaral, Miguel de (Tipgrafia Porto Medico, 1934)
Keywords: 1.Conservation 保護; 18.Bookworm; Fair

Fundamental English, Teacher's book IV - Ballard, Philip Boswood (Senior Series, 1934)
Keywords: Anglais (Langue) Composition et exercices; English language Composition and exercises; English language Study and teaching (Elementary)

The Holy Shroud of Turin - Barnes, Stapylton (Burns Oates and Washbourne Ltd., 1934)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Manual de Apologetica - Boulenger, A. (Livraria Apostolado da Imprensa, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Missoes Franciscanas Portuguesas de Mocambique e da Guine - Correia, P. M. Alves (Tip. das Missoes Franciscanas, 1934)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Ave Maria, a short commentary of the Hail Mary - Diether, Lawrence C. (The Carmelite Press, 1934)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Biblia da Juventude - Ecker, J (Edicoa da Uniao Grafica, 1934)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Catechism Made Easy, Being a Familiar Explanation of the Catechism of Christian Doctrine - Gibson, Henry (Burns Oates and Washbourne Ltd., 1934)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

L'annee Liturgique - Gueranger,Prosper (Maison Mame, 1934)
Keywords: 1.Conservation 保護; 2.Damage

A nossa lingua: livro de leitura para a 1.a, e 2.a classe dos liceus - Guerra, Abel (Livraria Apostolado da imprensa, 1934)
Keywords: Portuguese language; Portuguese language Readers; Readers (Publications)

Religion is Reason! - Hurley, Wilfred G. (The Paulist Press, 1934)
Keywords: 1.Conservation 保護; Good

Eugenio Goncalves Martins - Jalhay, Eugenio (Administracao da Broteria- Caixa Postal, 1934)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Eugenio Goncalves Martins - Jalhay, Eugenio (Administracao da Broteria- Caixa Postal, 1934)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

L'Ame russe - Legras, Jules (Ed. Emest Flammarion, 1934)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Supplement au Dictionnaire de La Bible - Louis Pirot (Librairie Letouzey et Ane, 1934)
Stamp of St. Joseph Seminary
Keywords: Good

Elementos Algebra - Neves, Francisco Ferreira (Imprensa da Universidade, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Elementos Algebra - Neves, Francisco Ferreira (Imprensa da Universidade, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

De Praeceptis dei et Ecclesiae - Noldin, H. (Typis et Sumptibus Feliciani Rauch, 1934)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

De Principiis, Theologiae Moralis - Noldin, H. (Typis et Sumptibus Feliciani Rauch, 1934)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Histoire des Papes Depuis La Fin du Moyen Age - Pastor, Louis (Librairie Plon, 1934)
Keywords: 1.Conservation 保護; 15.Stain 污漬

Mon Petit Catechisme - Rivier, M. A. Miss. Apost (Soc. Miss Etrangeres, 1934)
Keywords: 1.Conservation 保護; 2.Damage

Notae Exegeticae I, Loca Selecta Ex Epistolis Paulinis ad Usum Auditorum - Rosadini, S. (Apud aedes unversitatis gregorianae, 1934)
Stamp of St. Joseph Seminary
Keywords: 2.Damage; Cover damage

De Principiis Theologiae Moralis - Schmitt, A. (Typis et Sumptibus Feliciani Rauch, 1934)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

新解析幾何學 - Smith, Percey F.; Gale, Arthur; Neelley, John H. (商務印書館, 1934)
Keywords: Geometry; Géométrie; geometry; 幾何學

Antigo Testamento - Soares, Matos (Tipografia Porto Medico, Lda, 1934)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Biblia Sagrada, Antigo Testamento - Soares, Pe Matos (1934)
Keywords: 1.Conservation 保護; 2.Damage

Promptuarium Sacerdotis - Soengen, Ludovico (S. Sedis Apost. Editorum, 1934)
Keywords: 1.Conservation 保護; 2.Damage

Cantico de Amor, Versos - Vasconcelos, Bernardo de (Livraria Liturgica Editora, 1934)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

II Pars. Epistulae S. Pauli, Vol. III Epistula ad Hebraeos - Vitti. A (1934)
Stamp of the St. Joseph Seminiary
Keywords: 10.Cover Damage; 2.Damage

復興高級中學教科書 幾何學 - 余, 介石; 張, 通謨; 王, 雲五 (商務印書館, 1934)
Keywords: 几何 高中

新課程標準適用 初中幾何 (上冊) - 余, 介石; 徐, 子豪; 胡, 術五 (中華書局, 1934)

新課程標準適用 初中幾何 (上冊) 題解 - 余, 介石; 徐, 子豪; 胡, 術五 (中華書局, 1934)

高中幾何學教科書 上册 - 吴在渊; 胡敦复 (中華書局, 1934)
Keywords: 几何 高中

言文對照 東萊博議 第一冊 - 呂, 祖謙 (廣益書局, 1934)
Keywords: Zuo zhuan (Zuoqiu, Ming); Zuoqiu, Ming

言文對照 東萊博議 第二冊 - 呂, 祖謙 (廣益書局, 1934)
Keywords: Zuo zhuan (Zuoqiu, Ming); Zuoqiu, Ming

太虛法師文鈔初集. 第三編. 佛学 - 太, 虛 (中華書局, 1934)
Keywords: 佛教 文集 中国 民国

高級中學北新文選 (第二冊) - 姜, 亮夫 (北新書局, 1934)

高級中學北新文選 (第五冊) - 姜, 亮夫 (北新書局, 1934)

高級中學北新文選 (第六冊) - 姜, 亮夫 (北新書局, 1934)

樂國之王 - 張, 孝松 (聖体軍小叢書, 1934)
Keywords: 儿童文学 长篇小说 外国 现代

河西見聞記 - 明, 駝 (文藝彙刊, 1934)
Keywords: China Gansu Sheng; Gansu (Chine) Descriptions et voyages; Gansu Sheng (China) Description and travel; Ming, Tuo Journeys; Travel; Voyages and travels

經史百家簡編 - 曾国藩; 錢士民; 朱太忙 (大達圖書, 1934)
Keywords: Gu dian wen xue zuo pin zhong guo xuan ji

目錄學研究 - 汪, 辟畺 (商務印書館, 1934)
Keywords: Bibliographie Chine Histoire; Bibliography; Bibliography China History; China; History; 目錄學 歷史 中國

俞曲園書札 - 沈, 松泉; 何, 銘 (新文化書社, 1934)
Keywords: Authors, Chinese; Authors, Chinese Correspondence; Personal correspondence; Yu, Yue, 1821-1906; Yu, Yue, 1821-1906 Correspondence; Écrivains chinois Correspondance

人生學 - 王, 恩洋 (人生學, 1934)
Keywords: Fo xue yan jiu

儒学大義 - 王, 恩洋 (人生學, 1934)
比較中國, 印度, 西方三種不同形態的文化的特徵, 揉合儒, 佛兩家思想, 從勤勞刻苦, 節儉足用, 知足安分, 知名樂天, 仁義, 禮樂, 五倫, 三德中庸大道, 大人之學10個面向論述了儒家思想的特點
Keywords: Ru jia Zhong guo; 儒家 研究

大菩提論 - 王, 恩洋 (人生學, 1934)
Keywords: Fo xue yan jiu

解脫道論 - 王, 恩洋 (人生學, 1934)
Keywords: Fo xue yan jiu

詩學討論集 - 胡懷琛 (新文化書社, 1934)
Keywords: Chinese poetry; Chinese poetry History and criticism; Criticism, interpretation, etc; Poésie chinoise Histoire et critique

孔子家語 - 薛, 恨生; 鮑, 賡生 (新文化書社, 1934)

A Working English Grammar=活的英文法 - 詹, 文滸 (The World Book co. LTD, 1934)

中國文學史大綱 - 譚, 正璧 (光明書局, 1934)
Keywords: Chinese literature; Chinese literature History and criticism; Criticism, interpretation, etc; Littérature chinoise Histoire et critique

大學叢書 生物學實驗指導 - 鄭, 作新 (大學叢書, 1934)

化學 上冊 - 鄭, 貞文 (復興高級中學教科書, 1934)

復興高級中學教科書 生物学 - 陳, 楨; 王, 雲五 (商務印書館, 1934)
Keywords: 生物学 高中

蘇黃尺牘合刊 - 陳伯陶; 潘公昭.; 蘇軾; 黄庭堅 (大達圖書, 1934)
Keywords: Huang, Tingjian, 1045-1105; Huang, Tingjian, 1045-1105 Correspondence; Personal correspondence; Su, Shi, 1037-1101; Su, Shi, 1037-1101 Correspondence

奉獻 - 馬, 爾東 (聖體軍小叢書, 1934)
Keywords: 儿童文学-故事 法国; 故事-儿童文学 法国

Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1933)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Boletim Official da Colonia de Macau (1933)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Boletim Oficial da Colonia de Macau (1933)
Keywords: 10.Cover Damage; 2.Damage

Boletim Oficial da Colonia de Macau (Imprensa Nacional, 1933)
Keywords: 1.Conservation 保護; 18.Bookworm

Boletim Oficial de Macau (1933)
Stamp of Saint Joseph Seminary
Keywords: 1.Conservation 保護; Good

Collectanea Commissionis Synodalis (Kwantungtien Hutung, 1933)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

English Conversation Grammar=英語捷徑(前編) (The Commercial Press Limited, 1933)

Infancia de N. S. Jesus Cristo (Edicao e Propriedade do Autor, 1933)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Panem Nostrum Quotidianum, Manual de Piedade (Esc. Tipografica das Missoes, 1933)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Primeiros Elementos da Doutrina Crista (Tip. do Orfanato da Imaculada Conceição, 1933)
Keywords: 1.Conservation 保護; 18.Bookworm

Religiao e Patria (1933)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; Good

Religiao e Patria (1933)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; Good

Segundo Livro de Portugues para Chinese (Orfanato da Imaculada Conceição, 1933)

少年百科全書 (少年百科全書, 1933)
Keywords: Encyclopedias and dictionaries, Chinese

拉丁文詞學: 課本 = Elementa linguae Latinae exercitia : editio quarta (Institutiones Linguae Latinae, 1933)
Keywords: Latin language Grammar; Latin language Grammar Textbooks; Textbooks; 拉丁語 文法 課本

現存生物自然發生說之批評文錄 (中山大學理工學院生物系, 1933)
Keywords: Génération spontanée; Spontaneous generation

Curso de Historia de Portugal - Almeida, Fortunato de (Fortunato de Almeida, 1933)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Curso de Historia de Portugal - Almeida, Fortunato de (Fortunato de Almeida, 1933)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Dictionnare de Theologie Catholique - Amann, E. (Libraire Letouzey et Ane, 1933)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Institutiones Bibilicae, Scholis Accommodatae, De Libris Veteris Testamenti - Bea, Augustinus (E Pontificio Instituto Biblico, 1933)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Aux Portes de la Chine les Missionnaires du Seizieme Siecle 1514- 1588 - Bernard, Henri (En vente a la Procure de la Mission de Sienshien, 1933)
Keywords: 1.Conservation 保護; Fair

Aux Portes de la Chine les Missionnaires du Seizieme Siecle 1514- 1588 - Bernard, Henri (En vente a la Procure de la Mission de Sienshien, 1933)
Keywords: 1.Conservation 保護; Fair

De S. Liturgia Universim (Apud Carolum Beyaert, 1933)
Keywords: Good

Liturgicae Institutiones Tractatus Primus de Sacra Liturgia Universim - Callewaert, C. (Car. Beyaert, 1933)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Exercicio de Perfeicao e Virtudes Cristas - Clara, Pedro de Santa (Tip. da Uniao grafica, 1933)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Exercicio de Perfeicao e Virtudes Cristas - Clara, Pedro de Santa (Tip. da Uniao grafica, 1933)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Exercicio de Perfeicao e Virtudes Cristas - Clara, Pedro de Santa (Tip. da Uniao grafica, 1933)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Exercicio de Perfeicao e Virtudes Cristas - Clara, Pedro de Santa (Tip. da Uniao grafica, 1933)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Father Damien - Compton, Piers (Alexander Ouseley Limited, 1933)
Stamp of St. Joesph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Pene e Sanzioni Canoniche Estragiudiziali - Coronata, Matteo Conte Da Coronata (L I C E - R . Berruti & C., 1933)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Sainte Cecile et La Societe Romaine aux deux Premiers Siecies - Dom Gueranger (Pierre Tequi, Libraire-editeur, 1933)
Stamp of St. Joesph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

Sainte Cecile et La Societe Romaine aux deux Premiers Siecies - Dom Gueranger (Pierre Tequi, Libraire-editeur, 1933)
Stamp of St. Joesph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

A Virgem Prudente, Pensamentos e Conselhos - Doss, P. A. de (Edicoes do Apostolado da imprensa, 1933)
Signature
Keywords: 1.Conservation 保護; Good

Ponta Graca e a sua Igreja Paroquial - Ferreira Ernesto (Tip. do Diario Dos Acores, 1933)
Signature
Keywords: 1.Conservation 保護; Good

Gramática Inglesa - Ferreira, Júlio Albino (The teacher at home, 1933)
Keywords: English language; English language Grammar; English language Textbooks for foreign speakers Portuguese; Textbooks for Portuguese speakers

Dicionario ingles-portugues - Ferreira, Júlio Albino; Machin, James (Teacher at home, 1933)
Keywords: Dictionaries; English language; English language Dictionaries Portuguese

Epitome Theologiae Moralis - Ferreres, P. Ioannis B (Eugenio Subirana, 1933)
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover); 2.Damage

O Santo Sacrificio da Missa - Fontes, J. Ferreira (Edicoes do Apostolado da Imprensa, 1933)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

O Santo Sacrificio da Missa - Fontes, J. Ferreira (Edicoes do Apostolado da Imprensa, 1933)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Tips on Temptation - Fulkerson, Benjamin R. (The Queen's Work, 1933)
Keywords: 1.Conservation 保護; Good

A Minha Comunhao Diaria - Gomes, Alberto (Tip. e Enc., 1933)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 6.Yellowing 變黃.

De virtutibus theologicis - H. Lennerz (Apud Aedes Universitatis Gregorianae, 1933)
stamp of seminario de s. jose macau, sign, hand-writting
Keywords: 18.Bookworm; Good

增訂綜合英漢大辭典 = A comprehensive English-Chinese dictionary - Huang, Shifu; Jiang, Die (Commercial Press, 1933)
Keywords: Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language--Dictionaries--Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English, English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language--Dictionaries--English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; English language

Historia da Filosofia- Cours de Philosophie - Lahr, C. (Azevedo, Manuel L. C., 1933)
Keywords: 1.Conservation 保護; 2.Damage

Santa Teresa do Menino Jesus, 1873- 1897 - Laveille, Mons (Eidcao da Uniao Grafica, 1933)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Biblioteca Lusitana, Historica, Critica e Cronologica - Machado, Diogo Barbosa (Na Officina de Ignacio Rodrigues, 1933)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

Le Catacombe Romane, Opera Postuma - Marucchi, Orazio (La Libreria Della Stato, 1933)
Keywords: Good

Compendia de Meditacoes Para Todo o Ano - Monteiro, P. Manuel (Eidooes do Apostoland da Imprensa, 1933)
Stamp
Keywords: 1.Conservation 保護; 10.Cover Damage; 15.Stain 污漬; 2.Damage

Compendio de Meditacoes Para Todo o Ano - Monteiro, P. Manuel (Edicoes do Apostolado da Imprensa, 1933)
Signature
Keywords: 1.Conservation 保護; 15.Stain 污漬

Erros Mais Comuns da Lingua Portuguesa - Nunes, Francisco (Tip: Mercantil de N. T. Fernandes e Filhos, Ltda., 1933)
Keywords: 1.Conservation 保護; 14.missing area

Erros Mais Comuns da Lingua Portuguesa - Nunes, Francisco (Tip: Mercantil de N. T. Fernandes e Filhos, Ltda., 1933)
Signature
Keywords: 1.Conservation 保護; 14.missing area

Tratado Pratico de Analise Logica - Nunes, Francisco (Tip: Mercantil de N. T. Fernandes e Filhos, Ltda., 1933)
Signature
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 6.Yellowing 變黃

Tratado Pratico de Analise Logica - Nunes, Francisco (Tip: Mercantil de N. T. Fernandes e Filhos, Ltda., 1933)
Signature
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 6.Yellowing 變黃

Tratado pratico de analise logica - Nunes, Francisco (Mercantil de N. T. Fernande e Filhos, 1933)

The New American song book: (A century of progress in American song) (Hall & McCreary, 1933)
Keywords: Ballades anglaises; Ballads, English; Chansons folkloriques États-Unis; Folk songs; Folk songs United States; Musique populaire; National songs; National songs United States; Partitions (Musique); Popular music; Scores; Songs; Songs United States; United States

The Basic Words, A Detailed Account of Their Uese - Ogden, C. K. (Kegan Paul, Trench, Trubner & Co. Ltd., 1933)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Les Missions De Chine et Du Japon - Planchet, J. M. (Imprimerie des Lazaristes, 1933)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

祟修引 第三冊 - Rodriguez, P. A.; 劉, 准 (獻縣張莊天主教堂, 1933)

祟修引 第二冊 - Rodriguez, P. A.; 劉, 准 (獻縣張莊天主教堂, 1933)

Thesaurus of English Words and Phrases - Roget, Peter Mark (Grosset & Dunlap, 1933)
Keywords: 1.Conservation 保護; Good

De Revelatione Christiana - Sebastianus Tromp (Praelectiones dogmaticae, 1933)
stamp of seminario de s. jose macau
Keywords: 18.Bookworm; Good

Biblia Sagrada - Soares, Matos (Eseutado nas Oficinas Graficas, 1933)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Novo Testamento - Soares, Matos (Tipografia Porto Medico, Lda, 1933)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

朝拜聖體 - St Liguori; P. Ouang, C. M. (西什庫天主堂遣使会印字館: 北京救世堂, 1933)

O Santo Cura de Ars (1786-1859) - Vianey, Jose (Edicao da Uniao Grafica, 1933)
Signature
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

The New Method Readers - Reader 1A - West, Michael (Longmans, Green, 1933)
Keywords: Anglais (Langue) Lectures et morceaux choisis; Anglais (Langue) Étude et enseignement; English language Study and teaching; Readers

The New Method Readers - Reader 2 - West, Michael (Longmans, Green, 1933)
Keywords: Anglais (Langue) Lectures et morceaux choisis; Anglais (Langue) Étude et enseignement; English language Study and teaching; Readers

現代初中教科書 算術 - 嚴, 濟慈 (商務印書館, 1933)

崔東壁年譜 - 姚, 紹華; 何, 炳松 (中國史學叢書, 1933)
Keywords: China; Chronologies; Cui, Shu, 1740-1816; Historians; Historians China Chronology

史學常識 - 徐, 敬修 (大東書局, 1933)
Keywords: Historiography; 歷史學

徐氏高中公民 第一册 - 徐逸樵 (世界中學教本. 高級中學學生用, 1933)
Keywords: 公民教育 高中

平民字典 - 方毅 (商務印書館, 1933)
收字四千五百多個. 按筆畫多少編排
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries

作曲法初步 - 朱稣典.; 徐小濤. (開明書店, 1933)

梁質人年譜 - 湯, 中 (中國史學叢書, 1933)
Keywords: Liang, Fen, 1641-1729; 梁份, 1641-1729

最新口琴吹奏法 - 王, 慶勲 (商務印書館, 1933)
Keywords: Harmonica; Harmonica Methods; Harmonica Méthodes; Harmonica Studies and exercises; Harmonica Études et exercices; Methods (Music); Studies and exercises

物理學 上冊 - 周頌久 (商務印書館, 1933)
Keywords: Wu li xue; Zhong deng jiao yu

歐美列國 宗教教育之比較究 護教篇第四 - 袁承斌 (公教教育聯合会, 1933)
叙述法国, 意大利, 英国, 美国, 葡萄牙等国的教育状况及宗教教育的地位
Keywords: 宗教教育 对比研究 西方国家

實用藥物學 - 鄧, 立銘; 陳, 天樞 (商務印書館, 1933)

少年自然科學書叢 第二編 地球‧生物‧人 - 鄭, 貞文 (Commercial Press, 1933)

少年自然科學書叢 第十一編 蟲‧魚‧鳥‧獸 - 鄭, 貞文 (Commercial Press, 1933)

少年自然科學書叢 第十二編 衣‧食‧住‧行 - 鄭, 貞文 (Commercial Press, 1933)

少年自然科學書叢 第十編 燃料‧食料 - 鄭, 貞文 (Commercial Press, 1933)

少年自然科學書叢 第四編 雲‧雨‧風 - 鄭, 貞文 (Commercial Press, 1933)

語體文應用字彙 - 陳鶴琴 (Zhonghua jiao yu gai jin she cong kan, 1933)
本字滙是通過對常用字的調查滙集的. 編者閱讀554478字的各類材料, 收集重復出現率最多的異樣字4261個, 注明每字重復次數, 使讀者看出各字的使用率, 知道哪些字是常用字. 按部首編排
Keywords: Chinese language; Chinese language Glossaries, vocabularies, etc; Glossaries, vocabularies, etc

德華大字典 = Deutsch-Chinesisches Worerbuch - 黃, 異 (Commercial Press, 1933)
Keywords: Dictionaries; German languages Dictionaries Chinese

Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1932)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Boletim Oficial da Colonia de Macau (Imprensa Nacional, 1932)
Keywords: 1.Conservation 保護; 18.Bookworm

Breve Missal Romano dos Domingos e Feastas (Actividades Graficas, 1932)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Catalogo doS livros da Biblioteca do seminario de S. Jose (1932)
Keywords: 18.Bookworm

Catalogo doS livros da Biblioteca do seminario de S. Jose (1932)
Keywords: 18.Bookworm; 2.Damage; USJ SEMINARY LIBRARY PROJECT

DOSSIERS DE LA COMMISSION SYNODALE DIGEST OF THE SYNODAL COMMISSION (COMMISSION SYNODALIS IN SINIS, 1932)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Religion

Le Premier Successeur de Don Bosco (Librairie Catholique Emmanuel Vitte, 1932)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Litterae Encyclicae, Caritate Christi Compulsi (Cura Commissionis Syn. Editae, 1932)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

O Coracao de Jesus, Segunod a Doutrina de Santa Margrida Maria (Apostolado da Imprensa, 1932)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Religiao e Patria (1932)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Religiao e Patria (1932)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Statuta Generalia Actionis Catholicae Sinensis (1932)
Signature
Keywords: 1.Conservation 保護; 15.Stain 污漬

Exercicios Espirituais - Bernardes, Manuel (Tipografia Fonseca, 1932)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Summa Iuris Canonici - Cappello S. J. (Mariotti, 1932)
Stemp of St. Joseph Seminary
Keywords: Fair

A Consagracao das familias ao Sagrado Coracao de Jesus - Castello, A. C. (Ed. Apostolado da Imprensa, 1932)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Manuale Pietatis ad usum SAcerdotum et Clericorum - Chaudier, A. M. (Typis Societatis Missionum Ad Exteros, 1932)
Signature
Keywords: 1.Conservation 保護; 15.Stain 污漬

Jesus aos Pequeninos - Climaco, Joao (Tip. do Orfanato da Imaculada Conceição, 1932)
Keywords: 1.Conservation 保護; 18.Bookworm; Fair

Jesus Aos Pequeninos - Climaco, J. (Escola Tipografica do Orfanato, 1932)

Le Grand Saint du Grand Siecle-Monsieur Vincent - Coste, Pierre (1932)
Keywords: 1.Conservation 保護; 2.Damage

Resumo da Vida do Apostolo de Canara e Ceilao Veneravel Padre Jose Vaz - Dais, Euclides Rogaciano (Tipografia- Sadananda, 1932)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Parlez-vous français?: méthode directe. Cours préparatoire. 5e édition. Dessins de Myrac, Vialard .. - Deydier, Jules; Jolivet, Benoit; Guyot, Marcel (E. Vitte (impr. de E. Vitte), 1932)

A Perola das Virtudes - Doss, Adolfo de (Edicoes do Apostolado da Imprensa, 1932)
Stamp
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Liber usualis missae et officii pro dominicis et festis I. vel II. classis: cum cantu gregoriano ex editione vaticana adamussim excerpto et rhythmicis signis in subsidium cantorum a solesmensibus monachis diligenter ornato - Evang, S. Joannis (Typis Societatis S. Joannis Evangelistae, Desclée & Socii, 1932)
Keywords: Chant grégorien; Gregorian chants; Missals; Missels; missals

Fatima A Luz da Autoridade Eclesiastica - Fischer, Luiz (Of. Uniao Grafica, 1932)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Compendio de Teologia Ascetica e Mistica - Fontes, J. Ferreira (Edicoes do Apostolado da Imprensa, 1932)
Keywords: 1.Conservation 保護; Good

Esercizi latini: con regole ed osservazioni - Gandino, Giovanni Battista (Paravia, 1932)
Keywords: Lingua latina - Sintassi - Esercizi

Elementa Philosophiae , Aristotelico-Thomisticae - Gredt, Ios. (Herder & Co., Typographi Editores Pontificii, 1932)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

L'intellectualite hindoue - Mansion, Joseph (Rue des Recollets; Louvain, 1932)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Le Christ Dans Ses Mysteres, Conferences Spirituelles - Marmion, D. Columba (1932)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Trezena de Santo Antonio - Rolim, P. (Tip. Do. Boletim Mesal, 1932)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Mes de Maria - Sales, S. Francisco de (Tipografia Porto Medico, Lda, 1932)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

O Francês tal qual se fala: Novísima guia de conversação com a pronúncia figurada - Veiga, Adalberto (Primeiros passos nas linguas estranjeiras, 1932)

拉丁文初學: 話規 = Rudimenta Linguæ Latinæ Grammatica - Weig, D. G.; De Tsingtao, Apost.; Mittler, R. P. Th. (Typis Miss. cathol., 1932)
Keywords: 拉丁字母

General Biology - Wheat, Frank Merrill; Fitzpatrick, Elizabeth T. (American Book Company, 1932)
Keywords: Biologie; Biology; biology

文字學綱要 - 何仲英 (民智書局, 1932)
講述中國文字的起源, 甲骨文, 大篆, 小篆, 六書以及當代語和方言等. 高級中學用
Keywords: Chinese language Etymology; Chinois (Langue) Étymologie

中國文學史 - 劉, 麟生 (世界書局, 1932)

現代初中教科書 算術 - 嚴, 濟慈 (商務印書館, 1932)
Keywords: Arithmetic; Arithmetic Textbooks; Textbooks

高級中學北新文選 (第一冊) - 姜, 亮夫 (北新書局, 1932)

高級中學北新文選 (第三冊) - 姜, 亮夫 (北新書局, 1932)

高級中學北新文選 (第四冊) - 姜, 亮夫 (北新書局, 1932)

國音常用字彙 = Gwoin charngyonq tzyhhuey - 教育部國語統一籌備委員會 (商務印書館, 1932)
Keywords: Chinese language Phonetics; Chinese language Phonetics Dictionaries; Dictionaries

倫理學 - 謝, 扶雅 (世界書局, 1932)
Keywords: Lun li xue

新撰初級中學教科書 外國地理 (上冊) - 譚, 廉 (商務印書館, 1932)

插圖本中國文學史1 - 鄭, 振鐸 (古文書局, 1932)

插圖本中國文學史2 - 鄭, 振鐸 (古文書局, 1932)

插圖本中國文學史3 - 鄭, 振鐸 (古文書局, 1932)

插圖本中國文學史4 - 鄭, 振鐸 (古文書局, 1932)

生理衛生學 - 顧, 壽白 (現代初中教科書, 1932)

Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1931)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Apres La Conversion (Editions du Museum Lessianum, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Boletim Oficial da Colonia de Macau (Imprensa Nacional, 1931)
Keywords: 1.Conservation 保護; 18.Bookworm

Carta Enciclica do Santo Padre Pio XI (Esc. Tipo. Do Orfanato, 1931)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Champagnat (Societe de Saint Jean l'Evangeliste, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Joao de Deus (1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage

Le Bulletim des Missions (1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Litterae Encyclicae, Quadragesimo Anno, PII Papae XI (Cura Commissionis Syn. Editae, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Fair

Pastoral Colectiva, Decretos, Apendice (Tip. da Uniao grafica, 1931)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Selecta ex optimis latinitatis auctoribus, professoribus Societatis Iesu (Eugenius Subirana, 1931)
Keywords: Lengua latina

Dictionnare de Theologie Catholique - Amann, E. (Libraire Letouzey et Ane, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Fundamental English, Teacher's book II - Ballard, Philip Boswood (Senior Series, 1931)
Keywords: Anglais (Langue) Composition et exercices; English language Composition and exercises; English language Study and teaching (Elementary)

Novos Exercicios Graduados de Solfejos 1º Parte - Borba, Tomás (Valentim de Carvalho, 1931)
Keywords: Tonic sol-fa

De Breviarii Romani Liturgia - C. Callewaert, J. C. D. (Carolum Beyaert, 1931)
Keywords: 18.Bookworm; Good

A Actividade Missionaria da Companhia de Jesus, 1861-1931 - Casimiro, Acacio (Apostolado da Imprensa, 1931)
Keywords: 1.Conservation 保護; Good

Compendium Theologiae Dogmaticae - Christiano Pesch S. J. (Valkenburg, 1931)
Stamp of St. Joseph Seminary
Keywords: Poor

Compendium Theologiae Dogmaticae - Christiano Pesch S. J. (Valkenburg, 1931)
Stamp of St. Joseph Seminary
Keywords: Poor

Compendium Theologiae Dogmaticae - Christiano Pesch S. J. (Valkenburg, 1931)
Stamp of St. Joseph Seminary
Keywords: Poor

Selecta Ex Optimis Latinitatis Auctoribus vol. Primum - Cicero, M. T. (Eugenius Subirana, 1931)
Keywords: Literatura latina antologías

Sancta Teresinha do Menino Jesus e da Sagrada Face - Correia, Luis Maria Alves (Bibliotheca do Apostolado da Imprensa, 1931)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Le Grand Saint du Grand Siecle-Monsieur Vincent - Coste, Pierre (1931)
Keywords: 1.Conservation 保護; 2.Damage

Heure Sainte - Crawley-Boevey, R. P. Mateo (Rue De Picpus, 1931)
Keywords: 1.Conservation 保護; 18.Bookworm

宗教與社會正義 - Eddy, Sherwood (上海青年協會書局, 1931)

The Glories of Mary, by St. Alphonsus de Liguori - Grimm, Eugene (Andrew B. Kuhn, C. SS. R., 1931)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

Selecta portuguesa explicada - Guerra, Abel (Livraria Apostolado da imprensa, 1931)
Keywords: Littérature portugaise Étude et enseignement (Secondaire) Portugal; Portugal; Portuguese language Study and teaching (Secondary); Portuguese language Study and teaching (Secondary) Portugal; Portuguese literature Study and teaching (Secondary) Portugal

Relacao Anual das Coisas que Fizeram os Padres da Companhia de Jesus - Guerreiro, Fernao (Imprensa da Universidade, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Relacao Anual das Coisas que Fizeram os Padres da Companhia de Jesus - Guerreiro, Fernao (Imprensa da Universidade, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Manuel d'Histoire Ecclesiastique - Hedde, P. Rene (J. Gabalda et Fils Editeurs, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

De SS. Trinitate Schema Tractatus - Lohn, Ladislaus (Apud Aedes Universitatis Gregorianae, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

The story of Teresa Neumann - Pacificus (Burns Oates and Washbourne, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm

Histoire Des Papes - Poizat, Alfred (Librairie Plon : Plon-Nourrit et Cie, imprimeurs-éditeurs, 1931)
Stamp of St. Joesph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Histoire Des Papes - Poizat, Alfred (Librairie Plon : Plon-Nourrit et Cie, imprimeurs-éditeurs, 1931)
Stamp of St. Joesph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Historia da Companhia de Jesus na Assistencia de Portugal - Roddrigues, Francisco (apostolado da imprensa, 1931)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Historia da Companhia de Jesus na Assistencia de Portugal - Rodrigues, Francisco (Apostolando da Imprensa, 1931)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Der singende Alltag - Sambeth, Heinrich Maria (Pädag. Verl, 1931)

Vida Poular de S. Francisco Xavier - Schurhammer, p. Jorge (Apostolado da Imprensa, 1931)

Praelectiones Biblicae ad Usum Scholarum - Simon, R. P. Hadriano (Ex Off. Libraria Marietti, 1931)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Brevior Synopsis Theologiae Dogmaticae - Tanquerey, Ad. (Typis Societatis sancti Joannis Evangelistae, Desclée et Socii, 1931)
Keywords: 1.Conservation 保護; Fair

Brevior Synopsis Theologiae Dogmaticae - Tanquerey, Ad. (Typis Societatis sancti Joannis Evangelistae, Desclée et Socii, 1931)
Keywords: 1.Conservation 保護; 2.Damage; Fair

Nuove Meditazioni Pratiche - Vercruysse, P. Brunone (Casa Editrice Marietti fondata nel 1820, 1931)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

中國音樂小史 - Xu, Zhiheng; Wang, Yunwu (百科小叢書, 1931)
Keywords: China; Criticism, interpretation, etc; Music; Music China History and criticism

戰鬥綱要草案 - 何, 應欽 (中央陸軍軍官學校, 1931)
分7篇:戰鬥指揮, 攻擊, 防禦, 陣地戰, 追擊及退卻, 持久戰, 在特種地形之戰
Keywords: 战斗条令

現代初中教科書 物理學 - 周, 壽昌 (商務印書館, 1931)

大赦短經彙編 - 徐勱; 潘谷聲; 俞致中 (土山灣印書館, 1931)
Keywords: Catholic Church; Catholic Church Prayers and devotions; Prayers and devotions; Église catholique Prières et dévotions

經濟學 ABC - 李權時 (ABC 叢書社, 1931)
Keywords: Economics; economics; Économie politique

基本敎科書. 國語 - 沈, 百英 (Commercial Press (商務印書館), 1931)
Keywords: China; Chinese language; Chinese language Readers; Chinese language Study and teaching (Primary); Chinese language Study and teaching (Primary) China; Chinese language Textbooks; Readers (Publications); Textbooks

中國文學 - 隋, 樹森 (The World Book co. LTD (世界書局), 1931)

小宗徒 - 馬爾東; 陳, 田 (聖体軍小叢書, 1931)
本書為兒童電影故事
Keywords: 儿童文学-故事 法国; 故事-儿童文学 法国

近百年國際政治史略 - 馮, 節 (商務印書館, 1931)
Keywords: 1800-1999; Politique mondiale 19e siècle; Politique mondiale 20e siècle; World politics; World politics 19th century; World politics 20th century

Actas do Conselho do Governo (Imprnsa Nacional de Macau, 1930)
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Boletim Oficial da Colonia de Macau (1930)
Keywords: 1.Conservation 保護; 18.Bookworm

Boletim Oficial da Colonia de Macau (1930)
Keywords: 1.Conservation 保護; 18.Bookworm

Boletim Oficial da Colonia de Macau (1930)
Keywords: 1.Conservation 保護; 18.Bookworm

Curso de liturgia Romana (Revista Opus Dei, 1930)
Stamp of
Keywords: 18.Bookworm (Only Cover); Good

Elementa Grammaticae Latinae Ad Usum Tironum Sinensium (Typis Pei - Tang, 1930)
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; languages

Epistola Beati, Pauli Apostoli (1930)
Keywords: 1.Conservation 保護; Fair

Extraits Des Chants Sacres = 咏唱經文撮要 (A. M. D. G., 1930)
内收135首, 五线谱
Keywords: 宗教音乐-歌曲 选集 世界; 歌曲-宗教音乐 选集 世界

Les Conversions (Editions du Museum Lessianum, 1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage; 6.Yellowing 變黃

Manuel d'Histoire Ecclesiastique (1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Novena de Santa Teresinha do Menino Jesus (Desposito: Livraria Azevedo, 1930)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Recueil de Lettres = 法文尺牘輯要 (Pékin, Imprimerie des lazaristes, 1930)

Sanctum Jesu Christi Evangelium (1930)
Keywords: 1.Conservation 保護; Fair

Selecta Latina: Tipografia Fonseca (1930)

Vida de S. Bento, Contada as Almas Simples (edicao da revista Opus Dei, 1930)
Keywords: 1.Conservation 保護; 10.Cover Damage

辣丁文規: 文法 = Elementa grammaticæ Latinæ ad usum tironum Sinensium: Stylus (西什庫天主堂印書館, 1930)
Keywords: 拉丁语-语法; 语法-拉丁语

Synopsis Theologiae Dogmaticae - AD. Tanquerey (Typis Societatis sancti Joannis Evangelistae, Desclée et socii, 1930)
Stamp of unknown
Keywords: Fair

Santo Agostinho - Bertrand, Luis (Bibilioteca do Apostolado da Imprensa, 1930)
Stamp
Keywords: 1.Conservation 保護; 18.Bookworm (Only Cover)

Conferences de Notre-Dame de Paris - Boullaye, R. P. Pinard de la (Editions Spes, 1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Conferences de Notre-Dame de Paris - Boullaye, R. P. Pinard de la (Editions Spes, 1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Fastos da Companhia de Jesus, Restaurada em Portugual - Caismiro, Acacio (Tipografia Porto Medico, 1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Summa Iuris Canonici - Cappello S. J. (Mariotti, 1930)
Stemp of St. Joseph Seminary
Keywords: Fair

Zelia, Irma Maria Do. SSmo Sacramento - Castello, Alexandre Coutinho (Tip. Leitao- R. Da Picaria, 1930)
Stamp
Keywords: 1.Conservation 保護; Good

Pour etudier le Code de Droit Canonique - Cimetier, F. (Librairie Lecoffre, 1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

Guia do canto litúrgico (teoria e a prática) - De Menezes, Bruno (Tipografia Rangel, 1930)

Guia do Canto Litúrgico (Teoria e Prática) - De Menezes, Bruno (Tipografia Rangel, 1930)

中學法文文法 = Cours moyen de grammaire Francaise - edite par Fred Davis Aldrich, Irving Lysander Foster ; traduit et compile par Immin W. Lynn(凌望超); Aldrich, Fred Davis; Foster, Irving Lysander (La Presse Commerciale, 1930)
Keywords: Fa yu; Yu fa; Zhong deng jiao yu

Il Sepolcro di S. Stefano Protomartire, Scoperto a Beitgemal - Fergnani, G. (Societa Editrice Internazionale, 1930)
Keywords: 1.Conservation 保護; 2.Damage; 6.Yellowing 變黃

Fatima- A Lourdes Portuguesa - Fischer, Luis (Uniao Grafica, 1930)
Keywords: 1.Conservation 保護; 6.Yellowing 變黃

O Embaixador de Cristo - Gibbons, Caridal (Tip. da Grafica Conimbricense, Limitada, 1930)
Stamp
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Good

Relacao Anual das Coisas que Fizeram os Padres da Companhia de Jesus - Guerreiro, Fernao (Imprensa da Universidade, 1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

Biblioteca Lusitana, Historica, Critica e Cronologica - Machado, Diogo Barbosa (1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

O Beato Claudio de la Colombiere, da Companhia de Jesus - Magalhaes, Antonio de (Biblioteca do Apostolado da Imprensa, 1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair

Fundamentos de Religiao - Marquez, P. Gabino (Biblioteca do Apostolado da Imprensa, 1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Words From the Altar, Sermonettes on the Epistles and Gospels Combined - Monsignor Kolbe (Burns Oates and Washbourne Ltd., 1930)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Fatima, O Paraiso Na Terra - Montelo, Visconde de (Imp. of Uniao Grafica, 1930)
Keywords: 1.Conservation 保護; 2.Damage

Compendium Theologiae Dogmaticae - Pesch, Christiano (Herder & Co., Typographi Editores Pontificii, 1930)
Keywords: 1.Conservation 保護; 18.Bookworm; 6.Yellowing 變黃

改訂查理斯密小代數學 - Smith, Charles (商務印書館, 1930)
Keywords: Algebra; Algèbre; algebra

A Los Sacerdotes - Sulamitis, P. M. (Editorial Fides, 1930)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 2.Damage

Nuove Meditazioni Pratiche - Vercruysse, P. Brunone (Casa Editrice Marietti fondata nel 1820, 1930)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage; 6.Yellowing 變黃

愛的教育 - 亞米契斯著 ; 夏丏尊譯.; De Amicis, Edmondo; 夏丏尊 (世界少年文學叢刊 小說, 1930)
Keywords: Family life education; Family life education Italy Fiction; Fiction; Italy; Éducation à la vie familiale Italie Romans, nouvelles, etc

愛的教育 - 亞米契斯著 ; 夏丏尊譯.; De Amicis, Edmondo; 夏丏尊 (世界少年文學叢刊 小說, 1930)
Keywords: Family life education; Family life education Italy Fiction; Fiction; Italy; Éducation à la vie familiale Italie Romans, nouvelles, etc

詳訂古文評註全集: 卷十 下冊 - 劉, 豫庵 (錦章圖書局, 1930)
Keywords: Chinese prose literature; Prose chinoise

英漢模範字典: 求解作文兩用 = Model English-Chinese dictionary with illustrative examples - 張世鎏 (Commercial Press, 1930)
Keywords: Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language--Dictionaries--Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English, English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language--Dictionaries--English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; Dictionnaires multilingues; English language

布利氏新式算術教科書 - 徐, 金棠; 壽, 孝天 (Commercial Press, 1930)

西洋文學通論 - 方, 壁 (World Book Co. = 世界書局, 1930)

銅版精印四書集註 上冊 - 朱, 熹 (三興書局發行, 1930)
Keywords: Si shu; 四書

銅版精印四書集註 下冊 - 朱, 熹 (三興書局發行, 1930)
Keywords: Si shu; 四書

中國文學史綱 - 歐陽, 溥存 (Commercial Press (商務印書館), 1930)

中國文學提要 - 王羽 (The World Book co. LTD (世界書局), 1930)
按時代槪述上古至民國時期的中國文學
Keywords: Chinese literature; Chinese literature History and criticism; Criticism, interpretation, etc; Littérature chinoise Histoire et critique; Wen xue shi zhong guo

于斌主教抗戰言論集 - 益世報宗教文化社 (Catholic Truth Society (真理學會), 1930)
Keywords: Catholic Church. Pope (1878-1903 : Leo XIII); Church and social problems Catholic Church; Labor Religious aspects Christianity; Rerum novarum (Catholic Church. Pope (1878-1903 : Leo XIII)); Église et problèmes sociaux Église catholique; 天主敎 雜著; 社會學 理論